Precambrian to Paleozoic Tectonothermal Evolution in the Korla Area, Northern Tarim Craton, NW China - Ge, Rongfeng (Curtin University, 2014)
Systematic in-situ zircon U-Pb dating and Hf-0 isotopic analysis of zircon, together with whole-rock geochemical analyses, were carried out on Precambrian metamorphic rocks and intruding granitoids in the Koria area, northeastern Tarim Craton. Archean crustal evolution and geodynamic setting of the Paleoproterozoic and Neoproterozoic - Paleozoic tectonothermal events and their implications for the evolution of the Columbia and Rodinia supercontinents and the Central Asia Orogenic Belt are discussed and new models proposed.